Swine flu in children: clinical presentations, treatment and outcome in Birmingham, UK. (29th September 2015) - Hackett, S; Hill, L; Patel, J; Ratnaraja, N; Ifeyinwa, A; Farooqi, M; Nusgen, U; Debenham, P; Gandhi, D; Makwana, N; Smit, E; Welch, S
Abstract : Aims: In the early summer of this year, the reported cases of flu caused by the H1N1 recombinant influenza A virus rapidly increased across the world, including the UK. By early June, a third of UK cases were in the West Midlands. Methods: The authors retrospectively collected data on admitted children with confirmed swine flu in Birmingham in the summer of 2009. This was in order to capture the spectrum of clinical presentations seen in the first wave of the pandemic to benefit clinicians likely to encounter large numbers of cases during the second wave. Results: There were 89 admissions, with 78 case notes reviewed. 56% of admissions were male which was different to the adult data where a significant female predominance was noted. The age ranges were 0.1–15.7 years (median 5.7 years). Age did not correlate with the maximum temperature attained, number of symptoms present or duration of admission. Most children, with or without underlying disease, remained in hospital for one or more days. A huge diversity of presentations was seen, ranging from flu-like symptoms to febrile convulsions, epistaxis and intussusception. 41% of admissions did not fulfil HPA criteria; 19% did not have fever. The median C-reactive protein (CRP) was 10 mg/l (range <1–136 mg/l). CRP, lymphocyte or neutrophil counts did not differentiate patients with severe compared to mild disease or those patients with secondary bacterial infection. The highest inflammatory markers were in children without secondary bacterial infection. Significantly more children with underlying disease were treated with oseltamavir (68%) compared to those without (39%). This winter, patients have presented with flu-like symptoms of which many have had negative throat swabs or positive swabs for other viruses such as paraflu, metapneumovirus, respiratory syncytial virus and adenovirus, which are clinically indistinguishable. Conclusion: Inflammatory markers should not be relied upon as an indicator of disease severity or the presence of secondary bacterial infection. In view of the broad spectrum of clinical presentations and range of viruses currently causing flu-like symptoms, clinicians must be alerted to a wider range of differential diagnoses and remain open-minded.